Alpha decay in astrophysical environments (2019)
Different models for the description of the alpha decay process have been developed over the years. The alpha-decay has been a very active field of research since its discovery in the very beginning of the quantum era. In this thesis, the alpha-decay process is investigated in different astrophysical environments where the extreme conditions present can not be reproduced on Earth. To achieve this we study the effects of high temperatures (reached in supernovae), super strong magnetic fields (found in neutron stars) or the effects of nonlocality (due to the very nature of the quantum world) on the alpha-decay half-lives. The total potential between the alpha-particle and the daughter nucleus is found using the well-known density-dependent double folding model. This is an essential ingredient to evaluate the alpha-decay half-lives in our calculations. The half-lives of radioactive nuclei, calculated taking into account different external factors (temperature, magnetic field and nonlocalities) are compared with the half-lives found in the absence of such factors. It is mostly found that the alpha-decay half-lives get reduced when any of this factors is included. We point out the relevance of developing a model which takes into account these effects since alpha-decay half-lives are an important ingredient in the calculation of the abundance of heavy elements.